Síntese enantiosseletiva da sertralina: estudo e proposta de nova rota quimioenzimática - Mugnaini, Ingrid Christovam (2021)
Sertraline is one of the most important drugs in the psychotropic industry, and its use has been approved in the treatment of various psychological conditions. It belongs to the class of Selective Serotonin Reuptake Inhibitors (SSRIs), which act in order to increase the levels of serotonin in the synaptic cleft and are called selective because they do not have significant activity in other neurotransmitters. Its three-dimensional structure has two stereogenic centers, therefore, there are four stereoisomers: cis- (1S, 4S)-, cis-(1R, 4R)-, trans-(1S, 4R)- and trans-(1R, 4S)-, being only the first one of industrial interest. Enantiomeric purity is known in the industry as an important factor in guaranteeing the safety of the drug and, thus, the search for synthetic routes that results in products with high yield value and enantiomeric excess is growing. In this context, the present work presents and evaluates in detail the industrial synthesis of Zoloft®️, from its first synthetic route to the one currently used, in addition to two other chemoenzymatic proposals existing in the literature and suitable for green chemistry. At the end, a new chemoenzymatic proposal is presented, which has as main stage the Dynamic Kinetic Resolution of a secondary alcohol through enzyme (Candida antarctica lipase B) combined with an inorganic salt (vanadyl sulfate). This step is based on the methodology developed by Milagre Research Group for the enantioselective synthesis of chiral secondary alcohols and offers as main advantages the lower monetary investment, less damage to the environment and ease of handling, in addition to the possibility of recycling and reusing the catalysts.